Perancangan WhatsApp Blasting sebagai Sistem Recruitment di PT. Tuah Turangga Agung - Wibowo, Enrique; Bagus, Ujang; Andriani, Aulia; Rizki , Fachrezi; Hafidz , Muhammad; Pratama, Muhammad Yoga; Agustiyani, Noppy; Nugraha, Asep Erik (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
One of the developments in information technology in today's digital era is the design of information systems. According to this research, using WhatsApp Blasting can improve the performance of the recruitment system. The purpose of this research is to improve the manual method for recruitment. This research is based on design, which is followed by the need for a more automated recruitment process. Surveys and interviews were the data collection methods used to understand the problems faced in the conventional recruitment process. By using WhatsApp Blasting, prospective candidates can receive mass messages that help them communicate better and speed up the selection process. The results showed a decrease in time and cost as well as an increase in responsiveness and efficiency. This study supports the transformation of recruitment systems towards more automated and efficient methods. In addition, the platform provides convenience for both companies and candidates.